2011
DOI: 10.4278/ajhp.100709-qual-238
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of the Guiding Stars Nutrition Guidance Program

Abstract: PURPOSE . To describe the collaborative process between a grocery retailer and a panel of nutrition experts used to develop a nutrition guidance system (Guiding Stars) that evaluates the nutrient profile of all edible products in the supermarket, and to report the results of the food and beverage ratings. DESIGN . A collaboration between a private retailer and members of the scientific community that led to the development of a scoring algorithm used to evaluate the nutritional quality of foods and beverages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…An analysis of the program in 2011 demonstrated that of 27,466 grocery items, 24% earned at least one-star rating. 37,38 One star indicates good nutritional quality, two stars is better and three stars is best. Products with one, two, or three star ratings have lower levels of added sodium, saturated fat, trans fat, and added sugar, and more fiber, whole grains, vitamins, and minerals per calorie compared to items that do not earn a star rating.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of the program in 2011 demonstrated that of 27,466 grocery items, 24% earned at least one-star rating. 37,38 One star indicates good nutritional quality, two stars is better and three stars is best. Products with one, two, or three star ratings have lower levels of added sodium, saturated fat, trans fat, and added sugar, and more fiber, whole grains, vitamins, and minerals per calorie compared to items that do not earn a star rating.…”
Section: Methodsmentioning
confidence: 99%
“…The few that are not rated include new items (not yet rated), seasonal items (not consistently available) and items such as dried spices, dried coffee/tea and bottled water, which have no energy or nutrient content. For more information on Guiding Stars, see Fischer et al (20) . Hannaford Supermarkets is located in the north-east USA.…”
Section: The Nutrition Rating Systemmentioning
confidence: 99%
“…Analogous to the three-star approach recommended by the IOM, Guiding Stars assigned scores of zero, one, two or three stars (with three stars being the most nutritious) to specific branded food items based on an independent published algorithm that takes into account vitamins, minerals, fibre and whole grains (which raise the score), as well as saturated fat, trans-fat, cholesterol, added sodium and added sugars (which lower the score) (20) . A shelf tag beneath the product displays the number of stars assigned to that food item; one star indicates good nutritional value, two indicates better nutritional value and three indicates the best nutritional value.…”
Section: The Nutrition Rating Systemmentioning
confidence: 99%
“…Several nutritional symbols have been designed by various organizations to make it easier for consumers to identify healthier foods that meet set nutritional criteria and reflect the overall content of the food product. For example, the American Heart Association Heart Check programme in the USA allows companies meeting guidelines related to saturated fat and cholesterol to display the Heart Check symbol on their packaging (8) , while the National Heart Foundation in New Zealand administers a voluntary Pick the Tick symbol that companies can apply to display on their pre-packaged foods if they meet specific criteria related to the Ca, fibre, Na, sugar, saturated fat and total fat content of each product (9) . Some manufacturers have also developed their own nutritional symbols (i.e.…”
mentioning
confidence: 99%
“…Some manufacturers have also developed their own nutritional symbols (i.e. Kraft Sensible Solutions, Kellogg's Nutrition at a Glance) to indicate which of their products are healthier -although their criteria to determine 'healthier' varies (8) .…”
mentioning
confidence: 99%